One pot synthesis of 2- amino-5-oxo-4-aryl-5, 6, 7, 8-tetrahydro- 4Hchromenes- 3-carboxilic acid ethyl esters - Mahmud, Al; Halim, ME; Ali, MK; Kabir, MA; Akhter, K; Jahan, K; Romman, UKR (Bangladesh Journal of Scientific and Industrial Research, 2018)
Ethyl esters of 2-cyano-3-arylacrylic acid 1a-b ( a = 3- Br- C6H4, b= 4- OH- C6H4 ) reacted with 5, 5-dimethyl-1, 3-cyclohexane (2b, R = CH3) and 1c-d (c= 3- OH- C6H4, d= 3- NO2- C6H4 ) reacted with 1, 3-cyclohexanedione (2a, R = H) and 5, 5-dimethyl-1, 3-cyclohexanedione (2b, R=CH3) in the presence of alcoholic sodium ethoxide to give the corresponding ethyl esters of 2- amino- 7, 7- dimethyl-5-oxo-4-aryl-5, 6, 7, 8-tetrahydro- 4H- chromenes-3-carboxylic acid 3a-c, 3f and 2- amino-5-oxo-4-aryl-5, 6, 7, 8-tetrahydro- 4H- chromenes-3-carboxilic acid ethyl esters 3d-e. The structures of the compounds 3a-f were confirmed by their ultraviolet (UV), infrared (IR), 1H NMR, 13C NMR, mass spectra and elemental analyses. Bangladesh J. Sci. Ind. Res.53(1), 35-40, 2018